PENGELOLAAN LABORATORIUM DENGAN MODEL PROJECT-BASED LEARNING DI LABORATORIUM PRODI PENDIDIKAN BIOLOGI - Riska Septia Wahyuningtyas (Universitas Tribhuwana Tunggadewi, 2022)
This study aims to describe (1) planning (2) organizing (3) implementing (4) monitoring and evaluation at the Biology Education Laboratory, Faculty of Teacher Training and Education, Indonesian Christian University. The implementation of laboratory management was combined with a project-based learning model which is integrated into laboratory management courses. Laboratory management courses will assist in the description of implementation and supervision. This type of research was a case study with a qualitative approach. The methods used to collect data were observation, documentation, and questionnaires which were carried out to students who were taking laboratory management courses in the even semester of the 2022/2023 school year as many as 20 students. The results of the research showed as follows. (1) laboratory management planning including a 1-year work plan has not been implemented properly; (2) the organization of tools, materials, and laboratory administration has been carried out properly; (3) the implementation of the laboratory work program has been carried out properly; (4) supervision and evaluation carried out in the laboratory is carried out by the head of study program and the head of the laboratory at the end of each academic year; (5) the factors that influence laboratory management are the human resources in the laboratory and the available materials.